2006
DOI: 10.1002/pri.351
|View full text |Cite
|
Sign up to set email alerts
|

Are differences in leg length predictive of lateral patello‐femoral pain?

Abstract: The results suggested that the PALM method of measuring leg length differences may have clinical utility in differentiating between patients who are likely to sustain patello-femoral pain syndrome and those who will not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 35 publications
(45 reference statements)
0
7
0
1
Order By: Relevance
“…It has been implicated as a cause of a variety of medical conditions, including low back pain, trochanteric bursitis, osteoarthritis of the hip and knee, knee pain, and running injuries such as Achilles rupture. (2-10)…”
Section: Introductionmentioning
confidence: 99%
“…It has been implicated as a cause of a variety of medical conditions, including low back pain, trochanteric bursitis, osteoarthritis of the hip and knee, knee pain, and running injuries such as Achilles rupture. (2-10)…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Asymmetry in the kinetics of LLD-induced gait has also been linked to the etiology of plantar fasciitis, 7 lower back pain 8 and knee pain. 9 Concretely, LLD may play a key role in skeletal malalignment disorders such as patellofemoral conditions. 10 Asymmetries in the kinematics of human gait have been correlated with different degrees of anatomical LLD, 5 such as pelvic drop and hip adduction in the stance phase.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomic limb length discrepancy (ALLD) has been related to different orthopedic conditions, such as posterior tibial tendon dysfunction and hip osteoarthritis, due to an inadequate distribution of mechanical loads, 1,2 as well as gait kinematics asymmetries resulted from ALLD have been related to plantar fasciitis, 3 low back pain, 4 and anterior knee pain. 5 On the other hand, some studies have shown that limb length discrepancy (LLD) lower than 35 mm would not have a hazardous outcome in both function and etiology of orthopedic conditions. [6][7][8] Khamis and Carmeli 9 suggested that the controversy regarding the role of LLD on orthopedic conditions is related to the poor validity of measurement methods and the several abnormal biomechanical alterations that could be caused by LLD.…”
Section: Introductionmentioning
confidence: 99%